India and the SDGs - Nirupam Bajpai; John Biberman (Columbia University, Earth Institute, Center for Sustainable Development (CSD), 2020)
In 2015, the United Nations General Assembly passed UN Resolution 70/1, making achievement of the Sustainable Development Goals by 2030 official UN policy. Together, the 17 goals and 169 targets of the SDGs constitute a comprehensive agenda for sustainable development. The SDGs touch not just on environmental justice and intergenerational justice, but equitable economic growth and social stability, shaping development priorities around the needs of the disadvantaged, and designing just and robust institutions to strengthen coordination between sectors and build environments of accountability. India, for its part, has made great strides in meeting SDG targets related to climate change and sustainable consumption and production. More progress, however, must be made in reducing poverty and hunger, improving education, and promoting inclusive economic growth, and the country is seriously lagging when it comes to achieving gender equality and building inclusive and resilient infrastructure. Within India, the southern states of Kerala and Tamil Nadu have come closest to achieving the SDGs, particularly when it comes to social and economic goals. Various mountain and northeastern states have also performed well on SDG environmental targets. The northern states of the Gangetic Plain, collectively known as the Hindi belt, have overall made the least progress towards achieving the SDGs.
Keywords: 330